2011
DOI: 10.1007/s00540-011-1094-7
|View full text |Cite
|
Sign up to set email alerts
|

Epiglottic prolapse induced by lighted stylet tracheal intubation

Abstract: We report a case of epiglottic prolapse induced by lighted stylet tracheal intubation perceived by following upper gastrointestinal endoscopy. A 68-year-old male was to undergo endoscopic mucosal resection (EMR) under general anesthesia for a superficial orolarynx cancer spreading over the root of the tongue. Because the mucosal change was so minimal, intubation was performed with a lighted stylet instead of a direct laryngoscope, to prevent its metal blade spoiling the delicate endoscopic findings. After intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The hanging epiglottis may be the reason for urgent intubation or tracheostomy [1]. The flat and thin epiglottis may cause complications during intubation by interfering with the vestibule of the larynx [4].…”
Section: Discussionmentioning
confidence: 99%
“…The hanging epiglottis may be the reason for urgent intubation or tracheostomy [1]. The flat and thin epiglottis may cause complications during intubation by interfering with the vestibule of the larynx [4].…”
Section: Discussionmentioning
confidence: 99%
“…For any procedure, but specifically laryngeal surgery, intubation injury can be problematic for the surgeon and patient. Personal experience as well as reports in the literature prompted this study to determine the ease of intubation using a 5.0 ETT without a stylet . The assumption utilized in clinical practice, that the small, flexible ETT requires a stylet, is without confirmatory evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Personal experience as well as reports in the literature prompted this study to determine the ease of intubation using a 5.0 ETT without a stylet. 4,5 The assumption utilized in clinical practice, that the small, flexible ETT requires a stylet, is without confirmatory evidence. We found that most participants in our study could be intubated using a 5.0 ETT without a stylet, and none of these participants had laryngeal injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations